LEMBAGA PENDIDIKAN ISLAM DI INDONESIA: KAJIAN DESKRIPSI-ANALITIK MODEL LEMBAGA PENDIDILAN ISLAM - Maunah, Binti (IAIN Kediri, 2015)
Islamic educational institutions, in general, play a significant role in the world of education. Through a learningÃ‚Â process, these institutions should be able to bring students towards national education goals and become aÃ‚Â mirror for other educational institutions. This article attempts to examine Islamic educational intuitions, bothÃ‚Â formal and informal, in Indonesia focusing on their models. The discussion centers on two largest models ofÃ‚Â Islamic educations institutions in Indonesia, which pesantren (non-formal) and madrasah (formal). It is true thatÃ‚Â diversification of Islamic educational institutions supported with clear objectives and focused on professionaldifferentiation is a good, effective, and efficient way of education. Nevertheless, this article argues that suchÃ‚Â diversification will only lead to duplications, uselessness and ineffectiveness if the term means only pseudodiversificationÃ‚Â with outer and artificial purposes.Keywords: Lembaga Pendidikan Islam, Pesantren, Madrasah